Politik Hukum dan Reformasi Regulasi: Studi Komparatif Jerman dan Korea Selatan - Pebriana, I Kadek Ade; Hasibuan, Fanny Nafisah; Kartika, I Gusti Ayu Putri (Fakultas Hukum Universitas Islam Indonesia, 2026)
This study specifically examines the success of Germany and South Korea in legal policy, which has direct implications for the direction, form, and effectiveness of regulatory governance in respective countries. In that regard, to better understand the role of legal policy in regulatory governance, this study formulates two primary questions. First, how is the legal policy of legislation in Germany and South Korea formulated and implemented? Second, to what extent does this legal policy influence regulatory governance institutions? This study uses a normative legal research method considering the object of study relates to legal norms, principles, and opinions. The approach used is a comparative legal approach, with the basic concept of comparison being to identify similarities, differences, and relationships between the two countries. The theory used as an analytical tool is path dependency theory, to examine the background of legal policy and its implications for the outcomes of legal policy. The results show that strong legal policy encourages the formation of effective and contextual regulatory institutions, capable of addressing specific issues in each country. The Nationaler Normenkontrollrat (NKR) in Germany has successfully increased bureaucratic efficiency, while the Regulatory Reform Committee (PRC) and the Ministry of Government Legislation (MOLEG) in South Korea have ensured regulatory quality by minimizing political interests and increasing public participation. This study concludes that a well-formulated legal policy will create an effective, adaptive regulatory management institution capable of addressing multi-complex and multidimensional socio-economic challenges. Germany has succeeded with its bureaucratic efficiency approach, while South Korea has succeeded with its quality and public participation approach.